Scientific production on mobile information literacy in higher education : A bibliometric analysis (2006 - 2017) (2019)
ABSTRACT: This paper offers a bibliometric analysis of the scientific production on Mobile Information Literacy (m-IL) in Higher Education published between 2006 and 2017, taking into account papers covered by Web of Science (WoS), Scopus, Library and Information Science Abstracts (LISA), Library and Information Science and Technology Abstract (LISTA), and Education Resources Information Center (ERIC). Bibliometrics, as an integral part of research evaluation methodology, helps us to identify the subject’s evolution over the period studied. In this research we aim to: a) identify the most relevant journals that publish literature in this field, b) calculate the authors’ average productivity and identify the most productive authors, and c) discover the most significant trends in this academic field, through statistical and co-occurrence word analyses of the titles and the keywords used to index papers. The bibliometric results of this research provide a snapshot of the literature on Mobile Information Literacy that highlights the most relevant journals, authors, and trending keywords.